Germination and seedling growth of holm oak (Quercus ilex L.): effects of provenance, temperature, and radicle pruning - Caliskan, Servet (IFOREST-BIOGEOSCIENCES AND FORESTRY, 2013)
This study tested acorn characteristics and the germination behavior of different provenances of Holm oak (Quercus ilex L.) and the effects of radicle clipping of germinated acorns on 1-0 year-old seedling morphology and their field performances. The results revealed that all acorn characteristics among different provenances were significant. Quercus ilex acorns germinated well at alternating temperatures of 20/10 degrees C compared to a constant 20 degrees C temperature. Radicle clipping of Q. ilex significantly increased the shoot height and root collar diameter. The average number of main roots resulting from radicle clipping was 2.8 times more than unclipped treatment. The results can contribute to nursery practices and artificial regeneration of this species.
The following values have no corresponding Zotero field: pub-location: DEPT PROD VEGETALE, VIA ATENEO LUCANO 10, POTENZA, 85100, ITALY publisher: SISEF-SOC ITALIANA SELVICOLTURA ECOL FORESTALE
Keywords: artificial regeneration; Holm oak; Quercus ilex; Radicle Pruning; seed germination; sowing